NEW DOCUMENTS ON THE ACTIVITIES OF N.A. KATHANOV IN THE SUPREME BOARD OF THE NATIONAL ECONOMY OF THE USSR - H. B. MAMSIROV (Кавказология)
The personality of Nazir Kathanov is highlighted In the local historiography of Kabardino-Balkaria in the context of the temporary compromise between the Bolsheviks and the North Caucasian Shariah during the civil war, as well as his active role in the restoration of Soviet power in the region, and his activities as head of the Kabardino-Balkar Autonomous Oblast’s Representation at the All-Russian Central Executive Committee. Scattered information about his work as Commissioner of the National Department of the Main Economic Directorate of the USSR Supreme Economic Council for the North Caucasus is supplemented by new documents identified by the paper’s author in the collections of the State Archive of the Russian Federation and the Russian State Archive of Socio-Political History. It gives an expanded idea of N.A. Kathanov as a statesman of the North Caucasian and Union levels, and makes it possible to judge his professional competence, organizational and analytical abilities. New documents from the mentioned collections characterize N. Kathanov not only as a clergyman, but also as a secular person, not only as a military leader, but also as a creator, builder of a new life. And of course, he was not an enemy of the people, and the shameful label was glued to him undeservedly and slanderously. N. Kathanov passionately loved his land, all the peoples of the North Caucasus. He was well known, he was trusted and unanimously elected as the Commissioner. And this trust N. Kathanov fully justified.